Autoimmune Neurological Conditions Associated With Zika Virus Infection - Acosta-Ampudia, Yeny; Monsalve, Diana M.; Castillo-Medina, Luis F.; Rodríguez, Yhojan; Pacheco, Yovana; Halstead, Susan; Willison, Hugh J.; Anaya, Juan-Manuel; Ramírez-Santana, Carolina (Frontiers in Molecular Neuroscience, 2018)
Zika virus (ZIKV) is an emerging flavivirus rapidly spreading throughout the tropical Americas. Aedes mosquitoes is the principal way of transmission of the virus to humans. ZIKV can be spread by transplacental, perinatal, and body fluids. ZIKV infection is often asymptomatic and those with symptoms present minor illness after 3 to 12 days of incubation, characterized by a mild and self-limiting disease with low-grade fever, conjunctivitis, widespread pruritic maculopapular rash, arthralgia and myalgia. ZIKV has been linked to a number of central and peripheral nervous system injuries such as Guillain-Barré syndrome (GBS), transverse myelitis (TM), meningoencephalitis, ophthalmological manifestations, and other neurological complications. Nevertheless, mechanisms of host-pathogen neuro-immune interactions remain incompletely elucidated. This review provides a critical discussion about the possible mechanisms underlying the development of autoimmune neurological conditions associated with Zika virus infection.